Hyaluronic Acid and Radiofrequency in Patients with Urogenital Atrophy and Vaginal Laxity - Piotr Kolczewski; Mirosław Parafiniuk; Piotr Zawodny; Rashad Haddad; Agnieszka Nalewczyńska; Agnieszka Kinga Kolasa; Barbara Wiszniewska; Sophie Menkes; Alexander Bader; Giorgio Stabile; Nicola Zerbinati (MDPI AG, 2022)
Vaginal laxity (VL) and genitourinary syndrome of menopause (GSM), as well as aesthetic changes in the vulvar skin, often occur together and cause physical, psychological, and functional problems for women and their partners. The current study evaluated the efficacy of a nonsurgical radiofrequency device (RF) procedure combined with hyaluronic acid (HA) injection into the skin of the labia majora on clinical, histological, and aesthetic levels. Twenty women with GSM and VL, aged between 36 and 72 (mean age 53.4), were treated with bipolar RF SECTUM, vaginal and vulvar application, as well as with a hyaluronic acid (HA) injection into the skin of the labia majora. The Vaginal Laxity Questionnaire (VLQ), Vaginal Health Index (VHI), and Female Sexual Function Index (FSFI) were used to examine the clinical effects of the operations. The Global Aesthetic Improvement Scale was utilized to measure patient satisfaction. On a histochemical level, the concentrations of elastin and collagen in the vaginal wall and vulvar skin were examined. Results: There was significantly higher patient satisfaction and a considerable clinical improvement across all areas of analysis. On the histochemical level, elastin and collagen fiber concentration increased after the treatment protocol both in the vulvar skin and in the vaginal wall: elastin in the vaginal wall, 11.4%, and in the vulvar skin, 61%; collagen in the vaginal wall, 26%, and in the vulvar skin, 27%. The current study demonstrated the efficacy and safety of this nonsurgical RF procedure combined with a hyaluronic acid (HA) injection into the skin of the labia majora on clinical, histochemical, and aesthetic levels.